Hospitalization costs in Portugal among people with obesity: results from a nationwide population-based cohort 2011 to 2021 - Kelli Destri; Ana Rita Henriques; Nuno Mendonça; Joana Alves; Anabela Barcelos; Anabela Barcelos; Sara Simões Dias; Sara Simões Dias; Maria João Gregório; Maria João Gregório; Maria João Gregório; Helena Canhão; et al. (Frontiers Media S.A., 2024)
BackgroundObesity has been extensively studied over the years, primarily focusing on the physiological aspects of the disease. However, the general burden of obesity mainly the financial implications and its influence on hospitalization and length of stay have only recently garnered attention in the literature, particularly in the case of Portugal.AimThis study aimed to investigate the association between obesity and hospitalizations in the Portuguese adult population and compare the average costs of hospitalization among participants with and without obesity.MethodsAt baseline, the analytic sample consisted of 10,102 participants aged ≥18 years from the Portuguese population-based Epidemiology of Chronic Diseases Cohort (EpiDoC). Participants were then followed for up to 10 years from 2011 to 2021 in three more waves of data collection. Body mass index was derived from self-reported weight and height, and instances of hospitalization were self-reported by the participants. The associated costs for each hospitalization episode were categorized according to national legislation and valued according to the pricing for Diagnosis Related Groups.ResultsObesity was associated with more hospitalizations (for example, Obesity class I vs. normal weight: OR = 1.33 [1.14-1.55]). However, when the presence of multimorbidity was considered, this association diminished. While longer hospital length of stay was observed in individuals with higher obesity categories, this difference did not reach statistical significance. On average, the total hospitalization costs per patient with obesity amounted to €200.4 per year.ConclusionObesity is as a risk factor for hospitalizations and potentially with higher length of stay hospitalizations, with this effect being partially mediated by the concurrent presence of multimorbidity. Consequently, obesity constitutes an additional burden on healthcare systems. This underscores the imperative of implementing cost-effective prevention programs aimed at addressing and managing this significant public health concern.